2017
DOI: 10.1097/mat.0000000000000551
|View full text |Cite
|
Sign up to set email alerts
|

Osteogenic Differentiation of MSCs on Fibronectin-Coated and nHA-Modified Scaffolds

Abstract: The increasing demand for biocompatible bone substitutes has made it a priority to tissue engineering and regenerative medicine scientists. Combination of minerals, growth factors, and extracellular matrix (ECM) proteins with nanofibrous scaffolds is a potential promising strategy for bone reconstruction and clinical applications. In this study, nanohydroxyapatite (nHA) was incorporated in electrospun nanofibrous polycaprolactone (PCL) scaffolds coated with fibronectin (Fn). The potential bone regeneration cap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 28 publications
1
20
0
1
Order By: Relevance
“…Particularly, 5 μg·mL −1 of FNIII10-PA increased protein adhesion 3-fold compared with that of FNIII10. In many studies, PCL scaffold coated with FN remarkably enhanced cell adhesion, proliferation, and differentiation [ 23 , 24 , 25 ]. Drevelle et al found that the PCL film functionalized with RGD peptide (Ac-CGGNGEPRGDTYRAY-NH 2 derived from the bone sialoprotein) and easily adsorbed the serum adhesive proteins FN and vitronectin (VN), leading to increased cell adhesion and spreading by activating focal adhesion kinase (FAK) signaling [ 26 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Particularly, 5 μg·mL −1 of FNIII10-PA increased protein adhesion 3-fold compared with that of FNIII10. In many studies, PCL scaffold coated with FN remarkably enhanced cell adhesion, proliferation, and differentiation [ 23 , 24 , 25 ]. Drevelle et al found that the PCL film functionalized with RGD peptide (Ac-CGGNGEPRGDTYRAY-NH 2 derived from the bone sialoprotein) and easily adsorbed the serum adhesive proteins FN and vitronectin (VN), leading to increased cell adhesion and spreading by activating focal adhesion kinase (FAK) signaling [ 26 ].…”
Section: Resultsmentioning
confidence: 99%
“…FN was shown to have a powerful effect on both cell adhesion and differentiation of stem cells. For instance, Mohamadyar-Toupkanlou et al reported that nanofibrous PCL/HA scaffold coated with FN provided a suitable environment for proliferation as well as attachment and differentiation in mouse MSCs (mMSCs) [ 23 ]. Shekaran et al found that ECM-coated PCL microcarriers promoted human early mesenchymal stem cell growth, leading to cell expansion [ 24 ].…”
Section: Resultsmentioning
confidence: 99%
“…In two separate studies that conducted by our group, we demonstrated that PCL and pulsed electromagnetic field have a synergistic effect on osteogenic differentiation potential of MSCs and human induced pluripotent stem cells (iPSCs) (Ardeshirylajimi & Khojasteh, ; Arjmand, Ardeshirylajimi, Maghsoudi, & Azadian, ). In another study, we showed that nano‐HA and fibronectin (Fn) could increase osteoinductivity and osteoconductivity of PCL nanofibrous scaffold by culturing of MSCs and ectopic new bone formation (; Mohamadyar‐Toupkanlou et al, ; Mohamadyar‐Toupkanlou, Vasheghani‐Farahani, Bakhshandeh, Soleimani, & Ardeshirylajimi, ). Thompson et al developed the PCL performance by magnesium ferrite (Mg‐ferrite) based composite nanofibers was synthesized using an Electrospinning technique.…”
Section: Nanofibrous Fabrication Methodsmentioning
confidence: 99%
“…Considering the fact that stem cell research in Iran has grown quiet well, the research in the field of bone tissue engineering has grown as well using bone marrow mesenchymal , adipose , and Wharton's jelly derived stem cells for regeneration of bone.…”
Section: Bone Tissue Engineering In Iranmentioning
confidence: 99%